2023
DOI: 10.1002/adfm.202214007
|View full text |Cite
|
Sign up to set email alerts
|

Giant and Nonvolatile Control of Exchange Bias in Fe3GeTe2/Irradiated Fe3GeTe2/MgO Heterostructure Through Ultralow Voltage

Abstract: The discovery of van der Waals magnets has provided a new platform for the electrical control of magnetism. Recent experiments have demonstrated that the magnetic properties of van der Waals magnets can be tuned by various gate modulations, although most of them are volatile and require gate voltages no lower than several volts. Here, the realization of nonvolatile control of exchange bias and coercive fields in Fe3GeTe2/MgO heterostructures, and the gate voltage is as low as tens of mV which is two orders of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The above observations for the FGT nanoflake may indicate the coexistence of multiple magnetic phases rather than an individual FM phase, and so the reversal of magnetic moments is not at the same time, which enables the R xy – H curves to form double square-shaped hysteresis loops. Furthermore, the R xy – H curve at 200 K shows an obvious exchange bias effect, as shown in Figure S2, which is similar to the previous literature and indicates multiphase behavior. We deduce that there are some coupling effects between multiple magnetic phases in oxidized FGT, and coupling strength changes with temperature, resulting in double square-shaped hysteresis loops observed at temperatures above 180 K. When the temperature increases to 210 K, there is no hysteresis loop in the R xy – H curve, showing that the ferromagnetism of the FGT nanoflake disappears above its T C of 200 K.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The above observations for the FGT nanoflake may indicate the coexistence of multiple magnetic phases rather than an individual FM phase, and so the reversal of magnetic moments is not at the same time, which enables the R xy – H curves to form double square-shaped hysteresis loops. Furthermore, the R xy – H curve at 200 K shows an obvious exchange bias effect, as shown in Figure S2, which is similar to the previous literature and indicates multiphase behavior. We deduce that there are some coupling effects between multiple magnetic phases in oxidized FGT, and coupling strength changes with temperature, resulting in double square-shaped hysteresis loops observed at temperatures above 180 K. When the temperature increases to 210 K, there is no hysteresis loop in the R xy – H curve, showing that the ferromagnetism of the FGT nanoflake disappears above its T C of 200 K.…”
Section: Resultssupporting
confidence: 88%
“…The air exposure can effectively promote the formation of multiple magnetic domains in 2D FGT, but not in bulk FGT. 55 The previous literature has shown that O-FGT induced by oxidation of FGT nanoflakes in the ambient environment has antiferromagnetic phases, 51,54,56,57 and a skewed hysteresis loop has also been observed. 58 Moreover, the exchange bias effect has also been observed in oxidized FGT nanoflakes, which demonstrates that antiferromagnetic/ferromagnetic coupling forms at the interface between O-FGT and FGT layers.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most works on the electric control of magnetization in vdW magnets have focused on their magnetostatic properties, such as the magnetic anisotropy, saturation magnetization and Curie temperature, in both metallic 32 35 and semiconducting 21 25 materials. In contrast, their magnetization dynamics have only recently started to receive more attention, and have been studied using microwave-driven magnetic resonance 36 43 , or time-dependent magneto-optic techniques 44 52 .…”
Section: Introductionmentioning
confidence: 99%